Bridging the Gap in Neonatal Surgical Care in Low-Resource Settings: A Multimodal Approach Integrating Protocol-Based Care, Simulation Training, and Telemedicine (International Journal of Food and Nutritional Sciences, 2022)
Neonatal surgical care in low-resource environments is hampered by delayed diagnosis, insufficient infrastructure, and a shortage of trained personnel, leading to elevated morbidity and mortality. This study evaluates a multimodal intervention